Entrepreneurial management practices of school based cooperatives and economic development in Iloilo - Cipriano, Rosalinda; De Asis, Donna Marie; Gomez, Ian Lorenz; Magbanua, Glecerio; Sta Maria, Lourdes Christine (2017.)
Cooperatives, an integral part of the country's economic development as intended by the 1987 constitution (Castillo and Castillo, 2017), have indeed in recent years been flourishing especially. Commonly identified as champions of the lack-luster sectors of society such as farmers, construction workers, agricultural laborers and many more, cooperatives too have provided a significant amount of revenue into the nation and world economy at large (Schwettmann, 2014). As Scwettmann (2014) pointed out however, the underlying issue with cooperatives is the almost inherent to such a business. There's the challenge of size, of management incompetence, of innovation and of flexibility ; with the latter few commonly attributed to the lack of experience, exposure as well as unwillingness to deviate from traditional methods. The researchers in particular chose educational/school-based cooperatives as they have multiple functions and are more common and accessible compared to most. The main problem governing this study as well as the driving force of every action taken by the researchers was whether entrepreneurial management practices are a factor in some way in the level of impact of one educational cooperative to economic development of the geographical area by which the said cooperative constantly contributes to, in this case Iloilo City. Through purposive sampling technique, the researchers arrived at choosing ICPSTE MPC, WVSU MPC and IDCE MPC as the three main respondents of the study, each of which were given thorough questionnaires to answer. Results varied greatly but it is clear how positive entrepreneurial management practices have a significant impact on growth per se of an institution, specifically a cooperative ; and that such growth is attributable to economic growth of the local community.
Research Paper (Mgt 199-Business Resarch). -- [Iloilo City] : University of the Philippines Visayas-College of Management, December 8, 2017.